Understanding Impact of Seasonal Nutrient Influx on Sedimentary Organic Carbon and Its Relationship With Ammonia spp. in a Coastal Lagoon - Bhadury, Punyasloke; Sen, Areen (Frontiers in Marine Science, 2020)
Nutrient loading from land masses pose a serious threat to coastal ecosystem functioning. In this study the hypothesis involving applicability of a benthic foraminiferal genus, Ammonia as a reliable proxy for tracking sediment organic carbon load was evaluated in Chilika, Asia’s largest lagoon. In situ environmental parameters namely water temperature, pH, dissolved oxygen and salinity were measured from surface water and from sediment water interface along with measurements of dissolved form of nutrients from six stations of Chilika for a period of twelve months. Besides, sediment samples were collected and analyzed for elucidating total benthic foraminifer communities representing 0-2 cm fraction from all the above stations. Along with benthic foraminifera, pore water was extracted from 0-2 cm sediment from each station and subsequently analyzed to determine salinity, pH and dissolved form of nutrients as well as collected sediment (0-2 cm) from each station was analyzed for organic carbon (Corg) content including source characterization (stable isotope of δ13C) for the entire study period. Ammonia population representing live and dead ones was also enumerated from the surface of the sediment column. The investigation revealed that concentration of dissolved nitrate were high in both surface (Max. 86.25 µM, Min. 19.5 µM) and bottom (Max. 90.17 µM, Min. 26.75 µM) while in pore water it was higher in pre-monsoon month of June (Max. 131.67 µM, Min. 68.33 µM). Stable isotopic ratios of carbon (δ13C) from sediments varied within a narrow range (Max. -20.7, Min. -24.2) and did not exhibit any seasonal pattern but supported the idea of nutrient driven increased primary production. Organic carbon (Corg) content showed trends with seasonal oscillation during pre-monsoon (Max. 5.66 %, Min. 2.87 %) and post-monsoon months (Max. 3.88 %, Min. 2.66 %) in one of the studied stations. Out of 72 sediment samples, 46 samples had stained individuals of Ammonia spp. which were considered living at the time of collection, while 53 samples had dead specimens only. Pearson’s correlation co-efficient analysis showed that assemblages of Ammonia spp. were linked with sedimentary organic carbon and could be used as a reliable proxy for tracking sedimentary organic carbon in lagoons.